Smart human resource management and its impact on employee performance. A survey study of a sample of travel and tourism companies in Baghdad, Al-Saadoun Street (Czech Journal of Multidisciplinary Innovations, 2025)
This research aims to know the size of the relationship between research variables and are Smart Human Resources Management and Distinguished Performance in Travel and Tourism companies on the Sadoun Street in Baghdad. The study was conducted (50) sample for travel and tourism companies in order to discover the range of smart Human Resources Management, advanced analysis, and smart systems to support the level of strategic decisions, which are in different ways To raise the quality of services provided to tourists and to improve them, to raise the level of the Organization's tourism on creativity to achieve its long-term goals and adopted this study on the analytical descriptive approach, where all Selected data and sample information on travel and tourism companies on Al Saadoun Street in Baghdad, and analyzes it relying on a set of appropriate statistical methods to measure the effect of the removal of intelligent human resources management on distinguished performance, and the study reached A set of results of the most important and simple effect of smart human resources management in promoting outstanding performance, and smart technology used to develop human resources planning, raising the level of skills of the tourism organization, creating an appropriate ambience to participate in The process of making strategic decisions is faster and more accurate and the study also reached a set of recommendations that travel and tourism companies must adopt intelligent human resources systems, focusing on increasing attention to the purpose of raising the efficiency and development of their skills through Continuing training and upgrading smart digital infrastructure readiness in tourism companies to ensure their outstanding performance and achievement of sustainable competitiveness for these tourism companies.